(untitled) (Research, Society and Development, 2021)
Among the food waste are pumpkin peels and seeds, which can be turned into flour for alternative use as a source of nutrients. The objective of this work was to carry out a deep review of studies, indexed in the last 10 years (2011 to 2020), involving the bromatological and therapeutic characteristics of flours containing pumpkin residues (Cucurbita moschata) for use in food. For that, 4 databases were selected (BVS-LILACS, CAPES, Google Scholar and SciELO) using the terms “antinutrients of Cucurbites”, “nutrition Cucurbitaceae”, “benefits of C. moschata”, “residue of Cucurbita Moschata”, “pumpkin waste”, “pumpkin flour”, “pumpkin by-products”, “pumpkin co-products”, “pumpkin peel” and “pumpkin seed”. The results indicated that pumpkin waste flour is a good source of lipids, fibers, proteins, minerals, and antioxidants. It is concluded that pumpkin waste flour can be included in human and animal food as a functional and nutritional source, however studies are indicated to prove its therapeutic effects.